Situs Rumah Sandi: Sumber Pembelajaran Geometri Transformasi Berdasarkan Pendekatan Etnomatematika - Dinahyu Arifah Yuniar; Muhammad Prayito; Nurina Happy (Journal on Education, 2024)
This research aims to explore the understanding of ethnomathematics through the cultural context of the Rumah Sandi site in teaching transformation geometry mathematics. Ethnomathematics serves as a bridge between mathematics and culture, providing a valuable learning reference for students. The Rumah Sandi site holds historical significance as a monument of resistance during the Dutch Military Aggression II. In 2014, it underwent renovation by the Sandi Negara Institution and was renamed "Rumah Sandi Dukuh" as part of the Heritage Museum Sandi. The study employs a qualitative-exploratory ethnographic approach with data validity ensured through triangulation. Data collection methods include observation, interviews, and documentation. Various parts of the building exhibit geometric relationships such as dilation, reflection, and composition, which are found at the Rumah Sandi site. These findings can contribute significantly to enhancing the understanding of transformation geometry material in the context of mathematics education in schools